2002
DOI: 10.1007/s00424-001-0774-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced calcium release participates in cell volume regulation of rabbit TALH cells

Abstract: Changes of cell volume and intracellular calcium concentration ([Ca(2+)](i)) in immortalized thick ascending limb of Henle's loop (TALH) cells were monitored using confocal laser scanning microscopy and fura-2 fluorescence, respectively. Reduction of the extracellular osmolarity from 600 to 300 mosmol/l induced cell swelling followed by regulatory volume decrease (RVD). Simultaneously, the [Ca(2+)](i) increased transiently. The calcium rise was not observed in calcium-free solution or in the presence of nifedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…This hypothetical regime is supported by the observation that neither HaCaT keratinocytes nor TRPV4-transfected CHO cells showed any signs of [Ca 2+ ] i increase or RVD in Ca 2+ -free solution. Furthermore, in TALH cells or human cervical cancer cells, Ca 2+ influx was also necessary for RVD (Shen et al, 2001;Tinel et al, 2002). While this paper was under revision, Arniges et al (Arniges et al, 2004) showed that downregulation of TRPV4 using antisense oligonucleotides abolished RVD and Ca 2+ entry in a volumeregulating tracheal epithelial cell line.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This hypothetical regime is supported by the observation that neither HaCaT keratinocytes nor TRPV4-transfected CHO cells showed any signs of [Ca 2+ ] i increase or RVD in Ca 2+ -free solution. Furthermore, in TALH cells or human cervical cancer cells, Ca 2+ influx was also necessary for RVD (Shen et al, 2001;Tinel et al, 2002). While this paper was under revision, Arniges et al (Arniges et al, 2004) showed that downregulation of TRPV4 using antisense oligonucleotides abolished RVD and Ca 2+ entry in a volumeregulating tracheal epithelial cell line.…”
Section: Discussionmentioning
confidence: 90%
“…The ability to undergo RVD has been established for all three cell types (Tinel et al, 2002;Millar et al, 2004) (this report). Another volume-regulating cell type, HBE cells, has been shown to contain TRPV4 transcript as well (FernandezFernandez et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…SV40-transformed rabbit TAL cells obtained from rabbit kidney medulla were cultured as described (37). We have selected these cells for their fine structure and polar organization criteria by electron microscopy analysis.…”
Section: Methodsmentioning
confidence: 99%